2022
DOI: 10.1155/2022/7291250
|View full text |Cite|
|
Sign up to set email alerts
|

An Improved Secure Key Generation Using Enhanced Identity-Based Encryption for Cloud Computing in Large-Scale 5G

Abstract: The demand of cloud computing and 5G networks has increased in the current scenario due to their attractive features and also the security related to the data over the cloud. In the context of cloud security, there is a number of computationally hard methods available. One of the most popular methods used to secure data over the cloud is the identity-based encryption (IBE). It is an access policy that allows only authorized users to access legible data in order to avoid a malicious attack. IBE comprises of fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 40 publications
1
27
0
Order By: Relevance
“…In Doppler shift estimation, the proposed OIUKF-based estimation yields a decreased NMSE value of 0.00094, whereas other approaches such as EKFs, UKFs, and KLMS-(1) Set step sizes for TDEs and Doppler effects (2) Assign generation counter t � 1 and value for Max Gen//maximum generations (3) Assign initial population with step sizes of TDEs and Doppler effects (4) Repeat (5) Sort all the elephants according to their fitness via filter function (6) ci is the step size for all clans (7) ci do for all elephants j in the clan (8) Update xci, and generate xn, cj by equation ( 29), generate mutation is via mutation operator (9) if xci, j � xbest , ci then (10) Update xci, and generate xn, cj by equation ( 30) via step size in TDEs and Doppler effect (11) end if (12) end for (13) end for ( 14) Do this for all ci clans in the population (15) Get rid of the clan's worst elephant.ci by equation (32) and apply circle map (16) end for (17) Assess the population in light of the newly revised positions according to step size for TDEs and Doppler effect (18) modified NC give higher NMSE values of 0.36, 0.045, and 0.0092, respectively, after 5000 iterations in scenario 2 represented in Figure 4.…”
Section: Snr � H X K+1 􏼁mentioning
confidence: 99%
See 1 more Smart Citation
“…In Doppler shift estimation, the proposed OIUKF-based estimation yields a decreased NMSE value of 0.00094, whereas other approaches such as EKFs, UKFs, and KLMS-(1) Set step sizes for TDEs and Doppler effects (2) Assign generation counter t � 1 and value for Max Gen//maximum generations (3) Assign initial population with step sizes of TDEs and Doppler effects (4) Repeat (5) Sort all the elephants according to their fitness via filter function (6) ci is the step size for all clans (7) ci do for all elephants j in the clan (8) Update xci, and generate xn, cj by equation ( 29), generate mutation is via mutation operator (9) if xci, j � xbest , ci then (10) Update xci, and generate xn, cj by equation ( 30) via step size in TDEs and Doppler effect (11) end if (12) end for (13) end for ( 14) Do this for all ci clans in the population (15) Get rid of the clan's worst elephant.ci by equation (32) and apply circle map (16) end for (17) Assess the population in light of the newly revised positions according to step size for TDEs and Doppler effect (18) modified NC give higher NMSE values of 0.36, 0.045, and 0.0092, respectively, after 5000 iterations in scenario 2 represented in Figure 4.…”
Section: Snr � H X K+1 􏼁mentioning
confidence: 99%
“…Using Cramér–Rao limits, the study showed that, in cognitive radars, equal width subbands resulted in superior delay estimations than conventional radars. Cognitive radars performed effectively in terms of low SNRs in their investigation utilising Ziv-Zakai bounds [ 32 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Due to the recovery employed over the annotation words, the annotation process is tough and time-consuming, and it requires a significant amount of work to manually annotate the photographs. In the case of TBIR, the semantically zed text is not present [ 24 ]. Using an immersive image recovery technique combined with user term input as shown in Figure 2 , we may gather words from all sectors, increasing ambiguity while also increasing the likelihood of generating unrelated concepts [ 5 ].…”
Section: Existing Studymentioning
confidence: 99%
“…An efficient flood video surveillance system has been projected to observe as well as review the region where flooding is believed to be occurring in the course of better recordings in wireless ad-hoc surroundings. With the help of the CMT system in multihomed mobile networks, reliable video transmission can be achieved with the lowest delay [ 29 ]. The architecture view of the proposed system is illustrated in Figure 1 .…”
Section: Proposed Flooding High Definition Surveillance Using the Con...mentioning
confidence: 99%